Mechanical stresses originating from metal hydride composites during cyclic hydrogenation. (24th August 2015) - Heubner, Felix; Pohlmann, Carsten; Mauermann, Sebastian; Kieback, Bernd; Röntzsch, Lars
Abstract Metal hydride composites (MHC), which consist of a primary hydrogen absorbing phase and secondary phases such as graphite, offer very high volumetric storage densities and operation dynamics compared to widely used metal hydride powder beds. Here, we report on the stress evolution of confined MHC during hydrogen ab- and desorption which is due to the lattice expansion of the hydrogen absorbing phase during hydrogen uptake. The stress development during hydrogenation was recorded in situ using a specially designed measuring cell. Influences of gas pressure, temperature and MHC geometry on the stress evolution were considered. In this regard, so-called pressure-stress-isotherms are proposed for the first time in thermomechanical analogy to pressure-composition-isotherms.